Introducción a la genética en la enseñanza secundaria y bachillerato: I. Contenidos de enseñanza y conocimientos de los alumnos - Banet Hernández, Enrique; Ayuso, G. E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this paper an analysis is made of some of the causes which can hinder the students' learning of genetics at Secondary Level (12-17 years). This research study highlights the need of introducing changes in content at syllabus design level, and shows that students have a slight knowledge of heredity, although the basic tenets are very often wrong, even before they have their first contact with the subject as academic content at school.